Meningkatkan Keterampilan Berpikir Kritis Menggunakan Model PBL, Mind Mapping, dan TGT, Dengan Media Augmented Reality Siswa SD - Muhammad Alpian Chairani; Tika Puspita Widya Rini (Jurnal Pendidikan Sosial Dan Konseling, 2024)
This research was conducted at SDN Kuin Selatan 1 Banjarmasin class V because of the discrepancy between expectations and reality in learning science. The purpose of this research is to improve critical thinking skills, teacher activity, student activity, and student learning outcomes using PBL, Mind Mapping, and TGT learning models with Augmented Reality Media. This study included classroom action research, which was conducted four meetings. The results of the study have achieved success indicators for each aspect. With a teacher activity score of 28, the percentage of student activity is 91%, the percentage of critical thinking skills is 91%. Then the learning outcomes of students in each realm as a percentage also experienced completeness. Based on the results of this study it can be concluded that the PBL, Mind Mapping, and TGT models with Augmented Reality Media can improve critical thinking skills, teacher activity, student activity, and student learning outcomes.